Impact of drip fertigation on growth and yield of wheat in a conservation agriculture-based rice (Oryza sativa)-wheat (Triticum aestivum) system in eastern Indo-Gangetic plains of India - REDDY, K. SRIKANTH; PARIHAR, C M; PANNEERSELVAM, P; JAT, S L; SENA, D R; SHARMA, D K; PANDEY, RENU; DHAKAR, RAJKUMAR; SARKAR, AYAN; PATRA, KIRANMOY; BHARADWAJ, SNEHA; KUMAR, SUNIL; et al. (The Indian Journal of Agricultural Sciences, 2025)
A field experiment was conducted during 2022–23 and 2023–24 at the International Rice Research Institute-South Asia Regional Centre, Varanasi, Uttar Pradesh to assess the performance of wheat (Triticum aestivum L.) crop in 5-year long-term conservation agriculture (CA) based rice (Oryza sativa L.)-wheat (Triticum aestivum L.) system (RW) rotation using surface and sub-surface drip fertigation. The experiment was conducted in a randomized complete block design (RCBD) with nine treatment combinations and three replications. Results revealed that plant height, dry matter accumulation and leaf area index (LAI) of wheat at 30 days after sowing (DAS) showed non-significant differences across the imposed treatments. At 90 DAS, the highest plant height was observed in sub-surface drip fertigation (SSDF) and surface drip fertigation (SDF). Likewise, dry matter accumulation and LAI were higher at 90 DAS, in zero-till wheat (ZTW) under SSDF and SDF compared to ZTW with flood irrigation. Further, the study reveals that with 100% recommended dose of nitrogen (RDN) the grain yield of wheat was improved by 6% in ZTW plots followed by direct-seeded rice (DSR) plots compared to ZTW following PTR under flood irrigation plots. In addition, the SSDF and SDF resulted in yield increases of 24% and 20%, respectively as compared to CTW followed by PTR plots. Among the imposed treatments, ZTW-DSR-SSD-100N recorded the highest gross return (₹131,015) and net return (₹98,618), with the highest net BC ratio of 3.13, which is 8.5%, higher than the CTW-PTR-F-100N plots. These findings highlight the effectiveness of integrating DSR with drip fertigation technology in enhancing wheat productivity and economics under the CA-based RW system in the eastern Indo-Gangetic Plains.